Psicopatologia da despersonalização - Darcy M. Uchôa (Arquivos de Neuro-Psiquiatria)
1- From a clinical-nosographical point of view depersonalization appear in a pure state (relative), as a neurosis and in the neurosis, as a psychosis and in the psychosis. 2- Depersonalization can be defined as a state in which the patients feels different to what he was formerly in the body-ego, the psychic-ego and in his relation to the outer world. The terminology of Wernicke seems satisfactory: somatopsychic, autopsychic and alopsychic depersonalization (strangeness of the world or disrealization of Mapother-Mayer-Gross). 3- Depersonalization can reach partial aspects or the total body and psychic-ego; alienation or strangeness of this or that organ or part of the body or the whole body; the emotions, ideas, or volitions as the totality of the psyche. In extreme cases there arises the picture of the delusion of negation or phenomena of "double conscience" or multiple personality. 4- Approaching the cases of depersonalization with some neurological ones (hallucination of amputed limbs, anosognosia, autoscopia) brings certain explanations as to its neuro-pathogenic mechanisms. But here it is question, as Krapf shows, of instrumental phenomena farther away from the ego than authentic depersonalization (Krapf refers to the cases of disrealization with hemianopsia or hemianosognosia studied by Ehrenwald, von Stöckrt and Krapf). Besides this, the mere considerations of neuro-anatomo-pathological mechanisms (in the case still obscures) would not be able to explain the psychodynamic of the depersonalization. 5- In our cases the clinical examination (with many complementary proofs) was negative as to the existence of organic affection (in a strict sense) of the nervous system. In all of our patients (with much more evidence in the four first ones) we feel it is a question of "sickness of the personality" or, more precisely, "sickness of the ego". Very intense endo-psychic conflicts arise and - not being dissolved - impel the ego to the split. The satisfactory solution of such conflicts was followed by a cure in the first four cases. As was reported, eleven patients of our series had not responded to biological therapeutic (electrochocktherapy) or to psycho-surgical methods (frontal lobotomy). It was a question of depersonalization associated with grave psychosis in which our intention was above all to investigate problems of psychopathology and not so much of therapy. 6- We found the following mechanisms at the base of the depersonalization: a) conflict between hetero and homosexual tendencies interfering intensely in the character and behavior (first case) in which the necessity to reaffirm the own sex in situations strongly suggestive of contrary tendencies, provoked depersonalization (mechanism described by Oberndorf); b) intense conflict in the sense of rejection of the physical ego (feelings of inferiority) was observed in case (case 2) of a patient who forced herself to deny her body but immediately there arose emotional conflicts with the mother. The hetero and homosexual conflicts had connections with the identification with the father and the rejection of the feminine rôle. When she affirmed her own sex (feminine) by rejection of masculinity, arose depersonalization; c) in both cases the deepening of the analysis demonstrated, however, that the essential was more profoundly rooted. Indeed, an intense conflict arose between tendencies of strong dependence on the mother and many situations of rejection by her. There was a very deep situation of basic anxiety related to the fear of self-destruction by complete abandon (death). Such a mechanism arose with particular evidence in case 3 in which the patient rationalized the motives of hate but essentially mobilized the superficial aggression in order not to be invaded by the anxiety of death on account of the abandonment which she suffered in infancy. All this emotional constellation fell on the ego in the form of reversal of aggression in a degree so intense that the only adequate defence was the split (masochistic mechanism). 7- In many cases the split is not sufficient, even when processed at the most archaic levels by the effect of regression. Then, arise the "restitution mechanisms" (Freud) or "progression mechanisms" (Glover) as hallucinations, delusions, automatic phenomena of influence (transitivism), presenting the picture of depersonalization within the psychosis. This means greater weakness of the ego or greater intensity of conflicts. 8- In many cases we note the close relationship of depersonalization with hypochondria, considered as an increase in the investment of organs in detriment to that of objects. The repression by the countercathexis of the displeasing sensations can lead to feelings of alienation or strangeness, as shown by Tausk, Fenichel and others. However, also in these cases a deeper investigation always reveal the aggression impulses against immediate objects (considered as primaries objects) turned back against the ego. If hypochondria is a phenomenon of an increase of the narcisistic investment of the organ, the aggression component in organs symbolizing objects is also at times very evident. 9 - In neurotic depersonalization psychotherapy analytically oriented (exhuming the conflicts and solving them) or preferably psychoanalytic treatment is indicated. When depersonalization is part of the symptomatology of a psychosis, it accompanies the general indications of modern biologic techniques of shock and the modern methods of psychotherapy.